The Classical and Modern Concept of Unity in Arabic Poem - Khan, Yahya (Journal of Islamic and Religious Studies, 2016)
The issue of harmony and unity in the Arabic criticism and poem is of prime concern, which gained the great importance in modern criticism; as various critiques are of the different opinions regarding its existence, significance, applications and concepts even; in both ancient Arabic criticism and modern poetry. The present study will investigate to find out its roots in the ancient Arabic criticism and poetry; and to prove its references in modern Arabic criticism and poetry while indicating how this issue is kept alive by contemporary poets.